Effect of the Problem Based Learning and Double Loop Problem Solving Learning Models on Problem Solving Ability in Term of Creative Thinking on Environmental Pollution Material - Silva Ayu Indah Permata; Widha Sunarno; Harlita Harlita (Postgraduate, University of Mataram, 2022)
This type of research is quasi-experimental research that aims to 1) Determine the influence of problem-based learning (PBL) and Double Loop Problem Solving (DLPS) learning models on improving students' problem-solving ability. 2) Knowing the difference in the problem-solving ability of students with high creative and low creative thinking abilities. 3) Knowing the interaction of PBL and DLPS models with the ability to think creatively about problem solving. The population used in this study was grade VII students of state junior high schools in Lamongan Regency for the 2021/2022 academic year. The samples in this study consisted of 4 classes. The experimental class uses 1 PBL model for as many as two classes, and the experimental class 2 DLPS models for as many as two classes. Data collection using problem-solving ability test instruments and creative thinking test instruments. Hypothesis testing of the study using a two-way anava test with the study's results 1) There was no influence of the PBL and DLPS learning models on improving students' problem-solving ability. 2) there are differences in the problem-solving ability of students with high and low creative thinking abilities. 3) there is no interaction of the PBL and DLPS models with the ability to think creatively about students' problem-solving abilities.